1991
DOI: 10.1182/blood.v78.11.2982.bloodjournal78112982
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-related myelodysplastic syndrome and acute myeloid leukemia in children: correlation between chromosomal abnormalities and prior therapy

Abstract: We have studied 20 children with therapy-related myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML) who were 3 months to 16 years old at diagnosis of their primary neoplasm and 1 to 24 years old at diagnosis of their secondary neoplasm. The median interval from initial treatment for the first malignancy to diagnosis of therapy- related MDS or AML was 46 months (range, 12 to 116 months). Twelve patients had chromosomal abnormalities resulting in loss of material from the long arm of chromosomes 5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A search of the literature did not yield any reports of del(20q) in post-transplant MDS/AML. Chromosome 7 abnormalities, the most commonly reported cytogenetic aberrations in post-transplant MDS and alkylating therapy-related MDS, including cases associated with azathioprine therapy [16,27,30,31,46,48], were not detected in any of our patients.…”
Section: Discussionmentioning
confidence: 55%
“…A search of the literature did not yield any reports of del(20q) in post-transplant MDS/AML. Chromosome 7 abnormalities, the most commonly reported cytogenetic aberrations in post-transplant MDS and alkylating therapy-related MDS, including cases associated with azathioprine therapy [16,27,30,31,46,48], were not detected in any of our patients.…”
Section: Discussionmentioning
confidence: 55%
“…Deletions of chromosomes 5 and 7 were detected in both and are the most commonly found cytogenetic abnormalities after transplantation (Traweek et al , 1996; van Leeuwen, 1996). The latency period between the original diagnosis and MDS (119 and 239 months) was somewhat longer than the median of 33–48 months (range 12–116 months) found in studies of therapy‐related MDS/AML in children (Rubin et al , 1991; Farhi et al , 1993; Winick et al , 1993; Leahey et al , 1999b). Elapsed time between BMT and diagnosis of MDS was 72 and 108 months, respectively, and subsequent survival was 41 and 15 months respectively.…”
Section: Second Malignant Neoplasmsmentioning
confidence: 73%
“…Although the CCG‐2891 study could show no benefit in transplantion in first remission, stem cell transplantation may be a consideration for consolidation therapy for those with recurrent disease. Rubin et al (1996) found that among 27 DS patients with AML ( n = 11), ALL ( n = 14) or aplastic anaemia ( n = 2) 3‐year relapse‐free survival after transplant was 44% and death due to non‐leukaemic causes was 39%. Compared with non‐DS patients, those with DS appeared to be at risk of increased fatal pulmonary complications and airway problems requiring intubation.…”
Section: Acute Myeloid Leukaemiamentioning
confidence: 99%